Building marital foundations: A qualitative evaluation of reality therapy-based premarital counseling for young couples in Indonesia - Alwi, Muhammad Muhib; Prafitralia, Anisah (Institut Agama Islam Negeri Langsa, 2025)
This study evaluates the effectiveness of a Reality Therapy-based premarital counseling program for young couples, implemented through a local Office of Religious Affairs (KUA) in Indonesia. Premarital counseling is recognized as a strategic intervention to mitigate challenges associated with early marriage, such as emotional immaturity and inadequate conflict-resolution skills. Utilizing a qualitative descriptive design, this research investigated the counseling process and its perceived impact on marital harmony. Data were collected via in-depth interviews with religious counselors and young couples, participatory observations of counseling sessions, and document analysis. The findings indicate that the structured, stage-based Reality Therapy approach, focusing on building rapport, exploring present behavior, evaluating effectiveness, planning change, and committing to action, effectively enhanced couples' sense of personal responsibility, improved communication, and fostered joint future planning. The study concludes that integrating Reality Therapy principles into community-based premarital programs provides a practical and culturally resonant framework for empowering young couples. It recommends the broader adoption of this model within religious and community institutions as a strategic initiative to promote marital stability and build resilient families. This research contributes to the literature on applied counseling interventions in non-clinical, community settings, particularly within the context of early marriage prevention and support.